ETHNOBOTANICAL STUDY OF MEDICINAL PLANTS USED IN TRADITIONAL MEDICINE IN THE PROVINCE OF SIDI KACEM, MOROCCO - Fatima-zahra, Ennacerie; Fouzia, Rhazi Filali; Abdelilah, Rahou (Asian Journal of Pharmaceutical and Clinical Research, 2017)
An ethnobotanical study of medicinal plants was carried in the province of Sidi Kacem (Morocco), whose objective is to make an inventory of medicinalplants used in traditional therapy against respiratory, digestive, and cutaneous infections; also to describe their mode of use practiced by the localpopulation. The tool of the study was a questionnaire completed by 200 citizens of four investigated areas, determined by the stratified samplingtechniques, 40% practiced phytotherapy. The survey consists of a section on the informant, and another is interested in plants used by the population. The analysis of information has established a catalog of 73 species identified with their use of frequencies, partly used and the method of preparation.They belong to 39 families; the most dominant are Lamiaceae, Apiaceae, and Asteraceae. The leaves are the most used part in decoction to treat thethree types of infection mentioned above. These results allow us to create a database about this region's plants characteristic. They will be useful toestablish further studies on their chemical properties and biological activities. Keywords: Province of Sidi Kacem (Morocco), Phytotherapy, Ethnobotanical survey, Infections, Catalogue of plants.